Nursing regulation in Canada: Insights from a scoping review - Chiu, Patrick; Thiessen, Natalie J.; Idrees, Sobia; Leslie, Kathleen; Kung, Janice Y. (PloS one, 2025)
Canadian nursing regulators have implemented various innovations to reform regulatory approaches to address workforce challenges, system demands, governance reforms, and a drive for efficiency. Given the significant role that regulators play in influencing patient safety, workforce, and health system outcomes, decision-making must be evidence-informed. This review examined the nature, extent, and range of literature related to nursing regulation in Canada and how the existing scholarship aligns with emerging regulatory and health system trends to inform the development of a research agenda. The review was conducted following the JBI methodology for scoping reviews and with the support of a medical research librarian. A total of 195 sources, including scholarly (n = 156, 80%) and grey literature sources (n = 39, 20%), were included and reviewed. Just over half of the included scholarly sources were empirical studies (n = 80, 51.3%). The number of publications has steadily increased over the last few decades, and the majority of sources were situated in a provincial/territorial context (n = 104, 53.3%), followed by the national (n = 67, 34.4%) and global context (n = 24, 12.3%). The majority of the literature was led by scholars or professional groups unaffiliated with nursing regulators (n = 129, 66.2%). In contrast, nursing regulators led, commissioned, or were involved in a smaller portion of sources (n = 66, 33.8%). The largest category of literature focused on regulatory models, governance structures, and reforms (n = 59, 30.3%); followed by registration and licensure (n = 57, 29.2%); nursing roles and standards (n = 53, 27.2%); conduct, complaints, and discipline (n = 13, 6.7%); continuing competence programs (n = 11, 5.7%); and education program approval/accreditation (n = 2, 1%). The current literature base related to nursing regulation in Canada is largely descriptive and non-empirical and may not provide sufficient evidence to inform regulatory decision-making. This highlights opportunities for regulators and researchers to enhance collaboration to co-create research agendas that can maximize knowledge development and mobilization efforts.